The use of influencer marketing agency in company’s internationalization - Jämsén, Aarne Lauri Henrik (My University, 2022)
Influencer marketing has become a trendy marketing method in recent years, Influencer marketing is relatively new phenomenon, and its potential hasn’t been measured yet. Thus, marketers have started to identify people with great influence over others and have realized their market worth. In the 21st century, social media platforms have reached hundreds of millions new users, and at the same time word of mouth marketing have reached a new potential. Nowadays, consumers are able to read hundreds of online reviews, recommendations, and comments before making any consuming choices. Virtual communities are formed on multiple online platforms, and in these communities, there are always opinion leaders influencing others behavior. As the popularity of influencer marketing has risen, its use as part of internationalization haven’t yet been examined enough. Therefore, this paper studies usage of influencer marketing as part of internationalization. The study is conducted by examining the current literature on influencer marketing, consumer behavior, and internationalization. In addition, this paper provides a case study of an influencer marketing agency called Matchmade. The collected data was then analyzed by comparing it to the literature review. Findings of this study shows that usage of an influencer marketing agency can get a significant global coverage for advertisers’ campaign. As the case company’s customers are mainly gaming or other web placed application companies, the results show that for the most effective advertising campaign, companies should use a significant number of small content creators in their influencer marketing campaigns.
Keywords: influencer marketing; consumer behaviour; social media influencers; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business